Understanding the work experiences, coping strategies and organisational retention of social workers in Gauteng in-patient substance abuse treatment centres. - Vermeulen, Alexandrina (My University, 2009)
South Africa has experienced a drastic shortage of social workers. This shortage has affected many social welfare organizations, particularly those who offer services in the area of substance abuse. According to a recent study conducted by Earle (2008) many reasons could be ascribed to the high social work turnover, these include: poor working conditions; poor compensation of work; lack of resources and support; and increased demands for services. Hence, social workers are experiencing work stress, burnout and compassion fatigue taxing their personal and professional coping strategies which could lead to staff turnover. The primary aim of this study was to understand the work experiences, coping strategies and organisational retention of social workers in Gauteng inpatient substance abuse treatment centres. The study had an exploratorydescriptive design, incorporating both quantitative and qualitative paradigms to explore the work environment of the organisations and participants. Purposive sampling was used to select and divide the participants into three categories: entry level social workers; experienced social workers and social workers that had left the substance abuse field. Data was collected through conducting indepth interviews and through a questionnaire completed by the representatives from in-patient substance abuse treatment centres. This questionnaire was piloted with an in-patient treatment centre in KwaZulu Natal. The results of the quantitative data were analysed using descriptive statistics, which were illustrated via tables and figures and the qualitative data were analysed using thematic content analysis. The main findings of this study confirmed most of the reasons for work stress and burnout that may lead to staff turnover identified in previous studies by Ross (1997) and Earle (2008). These findings are incorporated into a retention model developed by the researcher. The model incorporated five stages: stage one focussed on the reasons for entering the substance abuse field (personal interests, undergraduate studies and/or accidental); stage two explored preparation of social workers by organisations after entry to the field; stage three identified four general factors that effects the sustainability of social workers (external/environmental influences, organisational factors, the type of client population, career opportunities and personal factors); stage four explained the individual differences in coping responses (negative or positive) to job stress either through fight responses, self-care strategies for retention or flight responses, staff turnover; lastly, stage five focussed on what organisations can do to reduce staff turnover. These findings can assist the occupational social worker to identify these retention challenges and develop strategies to reduce the risk of staff turnover.
Keywords: Work experience; Social workers; Substance abuse; Treatment centres